‘중국 신문읽기’ 수업의 PBL적용 사례 연구 - 오혜정(吳惠貞)(Oh Hye-Jung) (중국학(구중국어문론집), 2020)
본 연구는 중국 신문읽기 수업을 PBL에 적용한 사례로 기존의 언어교육 중심에서 한 단계 더 나아가 중국 지역학과 통상학에서 필요로 하는 기초적인 지식과 중국 사회에 대한 전반적인 이해를 돕고자 하는 것을 목적으로 하였다. 중국어 향상을 위한 어학적 측면의 이해와 중국 시장 진출 방안 모색이라는 실제 직무와 관련된 문제에 대한 해결방안을 제시하고, 정보수집능력, 지식습득능력, 자기주도적 학습 능력과 협동 학습 능력을 향상시키는 것을 교육 목표로 하고 있다. 문제제기, 수업설계, 평가의 과정을 통하여 학습자로 하여금 중국어에 대한 흥미를 유발하여 학습동기를 향상시키고, 중국신문이라는 기본 텍스트를 바탕으로 중국의 정치, 경제, 사회, 문화 등의 전반적인 부분을 이해하는데 PBL수업의 긍정적인 효과를 살펴볼 수 있을 것이다. As a case applying the Chinese newspaper reading class to the PBL, the purpose of this study is to help comprehensive understanding of basic knowledge and Chinese society required by Chinese local studies and commerce studies, going one step further from the existing focus on language education. This study aims at presenting solutions to problems related to the actual job of understanding the linguistic aspects and seeking ways to enter the Chinese market, and improving the information gathering ability, knowledge acquisition ability, self-directed learning ability and cooperative learning ability. Through the process of raising questions, designing lessons, and evaluating, this study will be able to examine the positive effects of PBL classes in enabling learners to increase motivation for class by inducing interests in Chinese language, and understanding the overall part of politics, economy, society, and culture of China based on fundamental text of Chinese newspaper. KCI Citation Count: 0